An examination of bank behavior around Federal Reserve stress tests - Cornett, Marcia Millon; Minnick, Kristina; Schorno, Patrick J.; Tehranian, Hassan (Journal of Financial Intermediation, 2020)
Examining bank behavior around Federal Reserve stress tests, we find that stress test banks increase capital ratios at the starting point for annual stress testing significantly more than non-stress test banks. These trends are completely reversed (and economically significant) in the other quarters. Further, the differences between stress test and non-stress test banks seen in stress test years do not occur in 2010, when the Fed did not conduct a stress test. Results show that, as they enter the stress test, stress test banks lower dividends significantly more than non-stress test banks. Finally, stress test banks spend significantly more on lobbying than non-stress test banks. The results suggest that stress test banks may be managing financial performance and investing in political spending to improve their chances of passing stress tests.